2018
DOI: 10.1051/0004-6361/201732086
|View full text |Cite
|
Sign up to set email alerts
|

Significantly high polarization degree of the very low-albedo asteroid (152679) 1998 KU2

Abstract: We present a unique and significant polarimetric result regarding the near-Earth asteroid (152679) 1998 KU 2 , which has a very low geometric albedo. From our observations, we find that the linear polarization degrees of 1998 KU 2 are 44.6 ± 0.5% in the R C band and 44.0 ± 0.6% in the V band at a solar phase angle of 81.0 • . These values are the highest of any known airless body in the solar system (i.e., high-polarization comets, asteroids, and planetary satellites) at similar phase angles. This polarimetric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 81 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…is not as steep as those of C-type asteroids, (101955) Bennu (Cellino et al 2018 ), (152679) 1998 KU 2 (Kuroda et al 2018 ), and ( 162173) Ryugu (Kuroda et al 2021 ). Because the polarization slope around the inversion angle is primarily dependent on the albedos but less dependent on particle sizes (Geake & Dollfus 1986 ), it is reasonable to hypothesize that 2005 UD and Phaethon have similar albedo values for the observed wavelength ( R C -band).…”
Section: Phase Angle Dependence Of Polarization Degreementioning
confidence: 92%
See 2 more Smart Citations
“…is not as steep as those of C-type asteroids, (101955) Bennu (Cellino et al 2018 ), (152679) 1998 KU 2 (Kuroda et al 2018 ), and ( 162173) Ryugu (Kuroda et al 2021 ). Because the polarization slope around the inversion angle is primarily dependent on the albedos but less dependent on particle sizes (Geake & Dollfus 1986 ), it is reasonable to hypothesize that 2005 UD and Phaethon have similar albedo values for the observed wavelength ( R C -band).…”
Section: Phase Angle Dependence Of Polarization Degreementioning
confidence: 92%
“…α 0 is sometimes notated as α inv in some literature. ( 2018 ), Lupishko et al ( 1995 ), Mukai et al ( 1997 ), Ishiguro et al ( 1997 ), Ishiguro et al ( 2017 ), Cellino et al ( 2018 ), Kuroda et al ( 2018 ), Kiselev, Rosenbush & Jockers ( 1999 ), and Kuroda et al ( 2021 ). (Zellner et al 1977 ) and the Meudon Observatory (Geake & Dollfus 1986 ).…”
Section: α 0 -P Min Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cometary dust particles are a major component of the interplanetary dust, for which interpretations of remote observations have progressively been proposed with the help of numerical and experimental simulations. Asteroidal dust particles can present some similarities with them, at least when primitive asteroids are considered; C-type asteroids typically present a low albedo, probably a high porosity (Housen et al, 1999;Kuroda et al, 2017) and a phase curve similar to comets (Hadamcik et al, 2009a). The composition of the samples in the experimental simulations with mixture of silicates, carbon-black and coal for the CC, low albedo of the particles (Hadamcik et al, 2007a) is consistent with the Rosetta findings for cometary dust properties revealing the presence of numerous complex organics (Fray et al, 2016), in very large particles made of sub-micron sized grains in aggregates either compact or with very high porosities (Langevin et al, 2016;Mannel et al, 2016).…”
Section: Interplanetary Cometary and Asteroidal Dust Particles Analomentioning
confidence: 99%
“…The reflected light is polarized, and by measuring the degree of polarization, one can estimate the size of the regolith on the surface. Kuroda et al (2018) observed an extremely low-albedo asteroid in 1998, KU 2 . They obtained linear polarization degrees of 44.6% and 44.0% at a phase angle (Sun-asteroid-observer angle) of 81.0 • in the Rc-and V -bands, respectively.…”
Section: Introductionmentioning
confidence: 96%